Effects of zirconia doping on additively manufactured alumina ceramics by laser direct deposition. (July 2020) - Pappas, John M.; Thakur, Aditya R.; Dong, Xiangyang
Abstract: The ability to additively manufacture functional alumina ceramics has the potential to lower manufacturing costs and development time for complex components. In this study, the doping effects of zirconia on laser direct deposited alumina ceramics were investigated. The microstructure of the printed samples was analyzed in terms of grain size and composition distribution. The addition of zirconia was found to accumulate along alumina grain boundaries and resulted in significant grain refinement. The zirconia doping largely reduced crack formation during processing compared to that of pure alumina samples. In the case of 10 wt% zirconia, cracking during deposition was nearly completely eliminated, but meanwhile porosity was increased. Through grain refinement and crack reduction in 10 wt% zirconia samples, bending strength was shown to increase by nearly four times the value obtained with pure alumina. Fracture toughness was also shown to increase by 1.5 times with addition of 5 wt% zirconia, which was attributed to the crack interaction with zirconia doped grain boundary and stress induced tetragonal to monoclinic transformation of zirconia. These findings indicated the potentials of dopants during laser direct deposition of ceramics and can further be used to tailor the properties of additively manufactured ceramic components. Graphical abstract: Unlabelled Image Highlights: Zirconia doping greatly reduced crack length during laser direct deposition of alumina ceramics. Doping helped substantially reduce grain size and critical flaw size within printed ceramics. Deposited ceramics were toughened due to crack interaction with zirconia doped grain boundary. Design by doping was an efficient way in tailoring properties of laser direct deposited ceramics.